A preliminary study on the diversity of pollen collected by stingless bee (Tetragonula aff. minor) in University of Indonesia campus area - Loeis, Triana Kamelia; Basukriadi, Adi (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
One of the stingless bee species that can be found in the University of Indonesia campus area is Tetragonula aff. minor. Therefore, research about T. aff. minor must be done to support conservation of campus’ natural ecosystem. Research was conducted to gather information about the diversity of pollen collected by T. aff. minor in the University of Indonesia, campus Depok area. Samples were collected in November 2019 from 0930 until 1330. Pollen samples were collected from the corbicula of stingless bees that traveling back to the hives. Pollen preparation was carried out by acetolysis method. After preparation, pollens were observed and counted under a light microscope in 100x and 400x magnifications. Result shows that T. aff. minor collected pollens from 10 taxa of plants; Asystasia gangetica (chinese violet), Caesalpinia pulcherrima (peacock flower), Carica papaya (papaya), Cocos nucifera (coconut), Dendrophthoe pentandra (mistletoe), Mimosa sp. (mimosa), Morinda citrifolia (noni), Lagerstroemia sp. (crape-myrtle), family of Cyperaceae, and Poaceae. Shannon-Wiener diversity index value is 1.431 and evenness value is 62.1%, therefore pollen collected by T. aff. minor has moderate diversity and evenness. Based on this study, it is known that T. aff. minor has polylecty diet spectrum and shows individual floral constancy during a foraging trip.